Resolutive Policy Model for the Settlement of Land Tenure Conflicts in National Strategic Projects: A Case Study of Rempang Eco City, Indonesia - Chandra Bhakti; Azhari Aziz Samudra; Rahmat Salam (Al-Makki Publisher, 2026)
This research examines land tenure and social conflicts arising from the Rempang Eco City National Strategic Project (NSP) on Rempang Island, Riau Islands Province, Indonesia. The goal is to identify the root causes of the conflict and propose a policy model to resolve land disputes in strategic development projects involving indigenous communities. A qualitative case study approach was used, with data collected through in-depth interviews, document analysis, and field observations, followed by thematic analysis using NVivo 12 software. The findings reveal that the Rempang conflict is a multidimensional issue rooted in structural inequality, marginalization of indigenous identity, and policy failures. The conflict reflects tensions between national economic development goals and the socio-cultural rights of indigenous communities over their traditional lands. Key factors driving the conflict include unclear land tenure, weak recognition of indigenous land rights, inadequate policy communication, limited public participation, and fragmented bureaucratic coordination. The conflict has been exacerbated by a security-based approach, leading to social and psychological impacts on affected communities. Drawing on policy implementation theories (Van Meter & Van Horn; Mazmanian & Sabatier) and conflict theories (resource conflict and identity conflict), the study proposes an Adaptive Collaborative Conflict Resolution Policy Model. This model emphasizes deliberative dialogue, recognition of local identity, agrarian justice, and adaptive policy implementation, providing a framework for resolving land tenure conflicts in National Strategic Projects and similar development contexts.